2022
DOI: 10.1128/spectrum.02515-21
|View full text |Cite
|
Sign up to set email alerts
|

LcCCL28-25, Derived from Piscine Chemokine, Exhibits Antimicrobial Activity against Gram-Negative and Gram-Positive Bacteria In Vitro and In Vivo

Abstract: The primary function of chemokines has been described as recruiting and activating leukocytes to participate in the immune response. Some chemokines are also broad-spectrum antibacterial proteins in mammals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…We found that the MIC of CCL20-His was 20 µM (Fig. 7c), which is in line with the MIC of other AMPs and chemokine-derived peptides [39][40][41] . These results confirmed that CCL20-His was an active antimicrobial chemokine.…”
Section: Bacteria Fail To Develop Resistance Against Antimicrobial Ch...supporting
confidence: 83%
“…We found that the MIC of CCL20-His was 20 µM (Fig. 7c), which is in line with the MIC of other AMPs and chemokine-derived peptides [39][40][41] . These results confirmed that CCL20-His was an active antimicrobial chemokine.…”
Section: Bacteria Fail To Develop Resistance Against Antimicrobial Ch...supporting
confidence: 83%
“…Cationic AMPs have various modes of action on bacteria . Most of them exert antibacterial effects primarily by physically disrupting membranes, dissipating electrochemical potential, inducing lipid asymmetry, and destroying important metabolites and cell components, resulting in cell atrophy and death . Binding to bacterial membranes is thought to be the first step in the interaction between AMPs and bacteria .…”
Section: Discussionmentioning
confidence: 99%
“…It is crucial for maintaining host-microbial homeostasis and for the host’s defense system against the invasion of numerous pathogens such as viruses, bacteria and parasites [ 1 , 2 , 3 ]. Antimicrobial peptides are a kind of polypeptides with antibacterial activity found in many organisms [ 4 ]. There are many kinds of antimicrobial peptides, which can be divided into animal-derived antimicrobial peptides, plant-derived antimicrobial peptides and microbial-derived antimicrobial peptides [ 5 ].…”
Section: Introductionmentioning
confidence: 99%